Using piezoresistive pressure sensors for resin flow monitoring in wind turbine blades. (2021) - Dimassi, Adli; Vargas Gleason, Minerva Gabriela; Hübner, Martina; Herrmann, Axel S.; Lang, Walter
Abstract: The production of large wind turbine blades is a costly and time-consuming process. In order to obtain high-quality products and to avoid dry spots, it is necessary to monitor the resin flow during the resin infusion process. Using piezoresistive pressure sensors to perform in-situ measurement of the pressure gradient gives live information about the textile impregnation status during the manufacturing process and enables instant reaction if some anomalies are discovered. In this work, the effects of the used sensors on the static mechanical properties and the fatigue behaviour of the used glass fibre composites were investigated. The sensors were used during the manufacturing of large sandwich panels similar to that used in wind turbine blades. It was found, that the used sensors do not degrade the mechanical performance of the used materials and they are able to measure the pressure gradient during the manufacturing of wind turbine blades and to give information about the progress of the resin front.